2003
DOI: 10.1038/sj.mp.4001350
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of rare dopamine receptor D4 alleles in children diagnosed with attention-deficit hyperactivity disorder

Abstract: Associations have been reported of the 7-repeat (7R) allele of the human dopamine receptor D4 (DRD4) gene with both the personality trait of novelty seeking and attention-deficit/ hyperactivity disorder (ADHD). The increased prevalence of the 7R allele in ADHD probands is consistent with the common variant-common disorder hypothesis, which proposes that the high frequency of many complex genetic disorders is related to common DNA variants. Recently, based on the unusual DNA sequence organization and strong lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 49 publications
5
150
2
Order By: Relevance
“…However, there is evidence to suggest that there may be an evolutionary advantage of the 7R allele and that it may even have a protective effect in ADHD. [42][43][44]60 The current finding supports this notion in that larger prefrontal gray matter volume is associated with variant alleles of the DRD4. Previously, we reported that the affected siblings in this sample display a tendency towards reduced prefrontal gray matter volume (significant for the right hemisphere).…”
Section: Discussionsupporting
confidence: 84%
“…However, there is evidence to suggest that there may be an evolutionary advantage of the 7R allele and that it may even have a protective effect in ADHD. [42][43][44]60 The current finding supports this notion in that larger prefrontal gray matter volume is associated with variant alleles of the DRD4. Previously, we reported that the affected siblings in this sample display a tendency towards reduced prefrontal gray matter volume (significant for the right hemisphere).…”
Section: Discussionsupporting
confidence: 84%
“…These data suggest that the absence of D 4 Rs is not sufficient to cause psychopathologies associated with heightened impulsivity and novelty seeking. Keywords impulsivity; D 4 receptors; mice; delay discounting; Go/No-go; inhibition; novelty seeking; locomotion Psychopathologies including pathological gambling (Comings et al, 2001), substance abuse (Vandenbergh et al, 2000), opiate dependence (Kotler et al, 1997), and attention-deficit hyperactivity disorder (ADHD; Faraone et al, 2001;Grady et al, 2003) are associated with the presence of dopamine D 4 receptor (D 4 R) gene (DRD4) polymorphisms. Novelty-seeking is often associated with these psychopathologies and is also observed in individuals possessing DRD4 alleles containing 7 repeats of a 48-nucleotide sequence (DRD4.7) (Benjamin et al, 1996;Ebstein et al, 1996Ebstein et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Further deep-sequencing of this genomic region may allow identification of the functional DRD4 variants directly involved in the genetic background of ADHD. In that regard, it is interesting to note that an increased burden of rare variants has been observed in the 7R allele of DRD4 in children with ADHD [Grady et al, 2003]. …”
Section: Discussionmentioning
confidence: 99%